Kinerja profitabilitas bank mega syariah berdasarkan analisis biaya operasional terhadap pendapatan operasional (BOPO) tahun 2020–2024 - santoso, muhammad irham imam; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the profitability performance of Bank Mega Syariah (BMS) during the period 2020–2024 using the Operating Expenses to Operating Income Ratio (BOPO) as the main indicator. This ratio measures the bank’s operational efficiency in generating income from its core activities. The data were obtained from BMS’s annual financial statements. The findings indicate significant fluctuations in efficiency, with 2021 recorded as the most efficient year (BOPO 39%), while 2023 marked the highest level of inefficiency (BOPO 65%). The variations in BOPO were influenced by changes in operational income, increases in administrative and personnel expenses, and adjustments in asset impairment allowance. These results highlight the importance of optimal cost management and strengthened revenue strategies to maintain the profitability of Islamic banks in the future. These results indicate that digital investments have a short-term impact in the form of increased costs, but begin to yield efficiency benefits in the long term.Furthermore, the pattern of changes in BOPO demonstrates a clear relationship between operational efficiency and profitability, with decreased efficiency potentially depressing financial health and company value, as emphasized in Islamic banking literature.